'Inching' towards interculturalism: ambiguities and tensions in teachers' ideologies and practices in the context of Cyprus. Issue 1 (2nd January 2020) - Hajisoteriou, Christina; Angelides, Panayiotis
ABSTRACT: This research examines teachers' conceptualisations of diversity and intercultural education. It also investigates the teaching approaches adopted by teachers within their culturally diverse classrooms. More specifically, the current project investigates the following research questions: how do teachers define and understand the concept of intercultural education; what practices do they adopt (or not) to promote intercultural education in their classrooms; what barriers do they perceive in their efforts to teach in more intercultural ways; what are their suggestions for implementing intercultural education in more successful ways? Observations and interviews took place with twenty teachers from ten schools in Cyprus. Our data shows that two ideological positions co-existed in teachers' discourses, namely: the monocultural approach (cultural-deficiency perspective), and the multicultural approach (cultural-celebratory perspective). We also examined how the ambiguities and contradictions in teachers' ideologies influenced their teaching and practices. In their daily routines, teachers seemed to adopt a teaching-as-usual approach, while occasionally engaging in 'intercultural moments', which included their rare attempts to differentiate or add cultural content to their teaching.